First Record of Red-headed Bunting (Emberiza bruniceps) from Deukhuri Valley, Lumbini Province - Kriti Chaudhary,; Leena Sah,; Anand Chaudhary, (Banko Janakari, 2026)
The Red-headed Bunting is considered a vagrant species in Nepal, with very few records from the country. We reported the first observation of this species from the Dang Deukhuri Foothill Forests and west Rapti Wetlands, an Important Bird and Biodiversity Area (IBA) located in Deukhuri, Dang District, southwestern Nepal. A total of seven individuals were observed, with one photographed on 16 April 2024, during a point-count survey of farmland birds. This is the westernmost known record of the species from Nepal. This finding underscores the importance of the IBA as a stopover for migrants using the Central Asian Flyway. The IBA remains largely unexplored, and a thorough survey of the birds and other biodiversity of the IBA is needed. Furthermore, based on data from recent observations of this species in Nepal and the IUCN criteria, we recommend that this species be reclassified from “Vagrant” to “Extant” and “Passage migrant” for Nepal.